Reserve Requirementson Foreign Currency Deposits in Sub-Saharan Africa : Main Features and Policy Implications - Kovanen, Arto. (Washington, D.C. : International Monetary Fund, 2002)
This paper reviews the reserve requirement arrangements of sub-Saharan Africa, focusing on the differences between reserve requirements on domestic- and foreign-currency deposits. The reserve requirement systems in sub-Saharan Africa are relatively simple and transparent, but in some countries high unremunerated reserve ratios impose a significant implicit tax on the banks. The currency denomination of the foreign-currency reserve deposits raises concern in countries undergoing large macroeconomic changes or experiencing exchange rate volatility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet